2009
DOI: 10.1097/pai.0b013e31817c02c6
|View full text |Cite
|
Sign up to set email alerts
|

Histologic, Immunohistochemical, and Molecular Classification of 52 IPMNs of the Pancreas

Abstract: IN pattern IPMNs were the most common. Mixed histology was common. K-ras mutations were most common, but did not correlate with dysplasia. p53 mutations were seen in 6% of cases (only in GF and PB subtypes). A HER2 mutation was found in a GF IPMN. EGFR and BRAF mutations were restricted to IN IPMNs. These findings suggest the possibility of alternate pathways for carcinogenesis between epithelial subtypes of IPMNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 23 publications
(58 reference statements)
1
55
1
3
Order By: Relevance
“…Recent papers support the hypothesis of distinct pathways for carcinogenesis among the different IPMN subtypes [3,4].…”
Section: Introductionmentioning
confidence: 89%
“…Recent papers support the hypothesis of distinct pathways for carcinogenesis among the different IPMN subtypes [3,4].…”
Section: Introductionmentioning
confidence: 89%
“…To our knowledge, this is the first report describing the relationship between invasiveness and TSP1 immunoreactivity in IPMN of the pancreas. Several investigators have reported clinicopathological and biological differences on comparing histologic subtypes of IPMN (5,12,13,17,20,25). Using the TSP1 expression pattern, we also analyzed differences in stromal invasion within histological subtypes of IPMN.…”
Section: References Discussionmentioning
confidence: 99%
“…Based on the results on an immunohistochemical study of TSP1, we investigated the therapeutic strategy according to the histological subtype of IPMN. Recently, there have been some reports on the relationship between the histological subtype and invasiveness in IPMN (5,12,13,17,20,25). We also analyzed the correlation between the subtype and stromal TSP1 expression in IPMNs to clarify which subtypes tended to achieve invasiveness fast and which tended to retain the status of adenoma in the pancreatic duct, and discussed the clinicopathological significance.…”
mentioning
confidence: 99%
“…The commonest of these is a somatic mutation at the oncogenic hotspots in KRAS which is identified in approximately 80% of IPMNs if sensitive techniques are used [8]. These KRAS mutations occur in all grades of dysplasia as well as histologic subtypes, and are not a predictor of the presence of high-grade dysplasia [9]. In contrast, loss of tumor suppressor genes occurs later in IPMN development.…”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%